Memelihara Keamanan dan Ketertiban Pilkada Serentak 2024 melalui Forum Silaturahmi Kamtibmas - Imron Rosyadi Hamid; Rr. Hesti Setyodyah Lestari; Sinollah (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
TThe Malang Resort Police held a Social Security and Community Service Forum (FSK) activity as a form of effort to maintain security and order ahead of the 2024 simultaneous regional elections. The activity was attended by a number of community leaders, the KPU, Bawaslu Malang Regency and all guests at the Bojana Puri building Jl. Raya Ngadilangkung Kepanjen on September 19 2024. through the activities of the Community Security and Order Silaturahmi Forum (FSK) it is hoped that it can increase synergy between the National Police, the community and all stakeholders in realizing Public Order and Order in the Malang Regency area so that it remains safe, smooth and conducive, so that the implementation of the Simultaneous Regional Elections on November 27, 2024 can run smoothly and not leave any conflict afterwards